Influences of nanoparticles on aquatic organisms: Current situation of nanoparticles effects in aquatic ecosystems - Gökçe, Didem (Sustainable Engineering and Innovation, 2021)
The quick improvement of nanotechnology permits a wide range of utilization of engineered nanoparticles, such as personal care products, medicals, optics, electronics, and automobiles. The nanoparticles manufactured from Ag, Au carbon-nanotube, ZnO, SiO2, TiO2, Cu, Ni, and magnetic ferrites are among the generally utilized in products. The nanoparticles are produced and utilized in large quantities and release into marine and freshwater ecosystems during production, use, discharge, treatment, and deposition. Those particles with a mean size of 1 nm - 100 nm are of potential environmental risks because of their particular qualifications and high reactivity although their great economical values. Based on the studies, the size, shape, and surface physical and chemical characteristics of the nanoparticles show the level of aggregation, solubility, structural and chemical composition, the importance of the use of nanoparticles, and their toxicity with biological systems. Nanoparticles can potentially cause adverse impacts on tissue, cellular, genetic materials, and protein- enzyme levels due to their unique physical and chemical qualifications. In this study, the effects of nanoparticles on aquatic organisms and aquatic ecosystems were evaluated.